2019
DOI: 10.1007/s11244-019-01169-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Active Phase Loading on the Hydrodeoxygenation (HDO) of Ethylene Glycol over Promoted MoS2/MgAl2O4 Catalysts

Abstract: The hydrodeoxygenation (HDO) of ethylene glycol over MgAl2O4 supported NiMo and CoMo catalysts with around 0.8 and 3 wt% Mo loading was studied in a continuous flow reactor setup operated at 27 bar H2 and 400 °C. A cofeed of H2S of typically 550 ppm was beneficial for both deoxygenation and hydrogenation and for enhancing catalyst stability. With 2.8-3.3 wt% Mo, a total carbon based gas yield of 80-100 % was obtained with an ethane yield of 36-50 % at up to 118 h on stream. No ethylene was detected. A moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…The amount of carbon deposited strongly depends on the time on stream (Figure 8). In line with previous reports [18,19], this is probably the main cause of deactivation. The severe carbon deposition is partly caused by a very high space velocity, which was chosen to facilitate steady state activity with a conversion below 100%.…”
Section: Investigation Of Catalyst Deactivationsupporting
confidence: 93%
See 4 more Smart Citations
“…The amount of carbon deposited strongly depends on the time on stream (Figure 8). In line with previous reports [18,19], this is probably the main cause of deactivation. The severe carbon deposition is partly caused by a very high space velocity, which was chosen to facilitate steady state activity with a conversion below 100%.…”
Section: Investigation Of Catalyst Deactivationsupporting
confidence: 93%
“…TEM (Figure S8) indicated that the deposited carbon was present throughout the spent catalysts, which is in agreement with previous findings [41]. The carbon appeared crystalline in agreement with Raman spectroscopy data on similar catalysts [18]. The lattice distances were analyzed by performing fast Fourier transforms of several crystalline areas in the TEM images of spent catalysts, which showed the presence of the MgAl2O4 support, and indicated the presence of crystalline carbon as well.…”
Section: Investigation Of Catalyst Deactivationsupporting
confidence: 90%
See 3 more Smart Citations